Effectiveness of Henan flood communication among opinion leaders on Douyin - Gan Liu; Mohamad Saifudin Mohamad Saleh; Miao Huang (Environmental Research Communications)
Periodic floods in China have been observed in recent years. While social media plays an essential role in disseminating flood information, limited research on the effectiveness of flood communication among opinion leaders in China. The specific characteristics, communication strategies, strengths, and weaknesses of the videos shared by opinion leaders remain ambiguous. The current study aims to explore the effectiveness of Douyin as a platform for opinion leaders in communicating flood crisis information by applying media richness and opinion leader theories. The main objective of this study is to examine the characteristic of flood information on Douyin, the communication strategies of flood information used by opinion leader, and the strengths and weaknesses of Douyin platform during flood communication. The results demonstrated that social media influencers were the most active opinion leaders in disseminating flood information, with short videos between zero and 15 seconds as the most popular communication format. In addition, hashtags and emoticons were essential communication strategies. While viral short videos were significant advantages of Douyin flood communication, rumours and fake news impeded the further development and spread of flood information. Summarily, this study significantly enriched the fields of crisis and environmental communication that received limited investigations in China previously.